In India, Psychiatry Has Come a Long Way* - Parikh, Rajesh (Mens Sana Monogr, 2015)
This Presidential Address of the Bombay Psychiatry Society covers the state of psychiatry in India in 1997. It posits that with the advent of newer brain imaging technologies in India such as computerised tomography, magnetic resonance imaging, single photon emission computerised tomography and brain electrical activity mapping, an era of evidence-based psychiatry in India has arrived. The Address cautions against the dehumanising potential of excessive reliance on technology. The need for a greater emphasis on psychiatry during undergraduate medical education is discussed along with the need to destigmatise psychiatric disorders. Finally, the need to encourage quality research in psychiatric disorders is stressed.